Pseudogenization of the cntQ permease confers distinct yersinopine-metal uptake selectivity in Yersinia species - Clémentine Laffont; Elizabeth Pradel; Laurent Ouerdane; Amélie Dewitte; Nicolas Oswaldo Gomez; Mathilde Tribout; Catherine Brutesco; Romé Voulhoux; Ryszard Lobinski; Florent Sebbane; Pascal Arnoux (BioMetals, 2026)
Yersinopine, a nicotianamine-like metallophore, was recently identified through biochemical analyses, but its in vivo production and functional role remain uncharacterized. In Yersinia pseudotuberculosis and its recent descendant Yersinia pestis , the cnt operon ( cntPQRLMI ) putatively encodes the biosynthesis and transport of yersinopine. In Y. pestis , however, two frameshift mutations disrupt cntQ , which encodes the predicted permease for yersinopine-metal complexes. This pseudogenization raises critical questions about the functional relevance of yersinopine in these closely related species. Here, we show that cnt operon expression is repressed by the zinc uptake regulator Zur and that both Y. pestis and Y. pseudotuberculosis secrete yersinopine under zinc-limited conditions. Unexpectedly, the operon mediates iron uptake in Y. pseudotuberculosis but supports zinc acquisition in Y. pestis . Moreover, targeted disruption of cntQ in Y. pseudotuberculosis shifts metal specificity from iron to zinc, mimicking the Y. pestis phenotype. Collectively, our results suggest that a single pseudogenization event could rewire metal uptake specificity. Our findings illustrate how evolutionary genome reduction can reshape bacterial physiology.

Draw me an oxidoreductase reacting with quinones - Marianne Broc; Michael V. Cherrier; Alexandre Uzel; Rodrigo Arias-Cartin; Pascal Arnoux; Gaël Brasseur; Farida Seduk; Bruno Guigliarelli; Stéphane Grimaldi; Pierre Legrand; Fabien Pierrel; Guy Schoen; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Bacterial adaptation to cold: Conservation of a short J‐domain co‐chaperone and its protein partners in environmental proteobacteria - Lana Weber; Atar Gilat; Nathanael Maillot; Deborah Byrne; Pascal Arnoux; Marie‐Thérèse Giudici‐Orticoni; Vincent Méjean; Marianne Ilbert; Olivier Genest; Rina Rosenzweig; Sébastien Dementin (Environmental Microbiology, 2023)
Bacterial genomes are a huge reservoir of genes encoding J‐domain protein co‐chaperones that recruit the molecular chaperone DnaK to assist protein substrates involved in survival, adaptation, or fitness. The atc operon of the aquatic mesophilic bacterium Shewanella oneidensis encodes the proteins AtcJ, AtcA, AtcB, and AtcC, and all of them, except AtcA, are required for growth at low temperatures. AtcJ is a short J‐domain protein that interacts with DnaK, but also with AtcC through its 21 amino acid C‐terminal domain. This interaction network is critical for cold growth. Here, we show that AtcJ represents a subfamily of short J‐domain proteins that (i) are found in several environmental, mostly aquatic, β‐ or ɣ‐proteobacteria and (ii) contain a conserved PX 7 W motif in their C‐terminal extension. Using a combination of NMR, biochemical and genetic approaches, we show that the hydrophobic nature of the tryptophan of the S. oneidensis AtcJ PX 7 W motif determines the strong AtcJ–AtcC interaction essential for cold growth. The AtcJ homologues are encoded by operons containing at least the S. oneidensis atcA , atcB , and atcC homologues. These findings suggest a conserved network of DnaK and Atc proteins necessary for low‐temperature growth and, given the variation in the atc operons, possibly for other biological functions.

Comparative genomic analysis provides insights into the evolution and niche adaptation of marine M agnetospira sp. QH ‐2 strain - Boyang Ji; Sheng‐Da Zhang; Pascal Arnoux; Zoe Rouy; François Alberto; Nadège Philippe; Dorothée Murat; Wei‐Jia Zhang; Jean‐Baptiste Rioux; Nicolas Ginet; Monique Sabaty; Sophie Mangenot; et al. (Environmental Microbiology, 2014)
Summary Magnetotactic bacteria ( MTB ) are capable of synthesizing intracellular organelles, the magnetosomes, that are membrane‐bounded magnetite or greigite crystals arranged in chains. Although MTB are widely spread in various ecosystems, few axenic cultures are available, and only freshwater M agnetospirillum spp. have been genetically analysed. Here, we present the complete genome sequence of a marine magnetotactic spirillum, M agnetospira sp. QH ‐2. The high number of repeats and transposable elements account for the differences in QH ‐2 genome structure compared with other relatives. Gene cluster synteny and gene correlation analyses indicate that the insertion of the magnetosome island in the QH ‐2 genome occurred after divergence between freshwater and marine magnetospirilla. The presence of a sodium‐quinone reductase, sodium transporters and other functional genes are evidence of the adaptive evolution of M agnetospira sp. QH ‐2 to the marine ecosystem. Genes well conserved among freshwater magnetospirilla for nitrogen fixation and assimilatory nitrate respiration are absent from the QH ‐2 genome. Unlike freshwater M agnetospirillum spp., marine M agnetospira sp. QH ‐2 neither has TonB and TonB ‐dependent receptors nor does it grow on trace amounts of iron. Taken together, our results show a distinct, adaptive evolution of M agnetospira sp. QH ‐2 to marine sediments in comparison with its closely related freshwater counterparts.